Solid-liquid phase equilibrium and thermodynamic properties analysis of paliperidone palmitate in 21 kinds of mono-solvents. (June 2023) - Yu, Shuai; Wang, Zihao; Yu, Panpan; Wang, Shanshan; Li, Guangzhou; Xue, Fumin; Fu, Long
Graphical abstract: Highlights: Solubility data of paliperidone palmitate racemic mixture in 21 kinds of mono-solvents were determined. Different thermodynamic models were used to correlate solubility data. Solubility increases with the increasing of temperature. Dissolution properties of paliperidone palmitate were calculated based on the Wilson model. Abstract: Solid-liquid equilibrium solubility paliperidone palmitate (PP) in 21 kinds of mono-solvents, including ethanol, n -propanol, i -propanol, n -butanol, i -butanol, s -butanol, n -pentanol, i -pentanol, 2-butanone, methyl isobutyl ketone, cyclohexanone, ethyl formate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, amyl acetate, N, N -dimethylformamide (DMF), tetrahydrofuran (THF), toluene, and 1, 4‑dioxane were determined by a gravimetric method at a various temperature. The solubility of PP increases with the increase of temperature. In alcoholic solvents, the solubility order is: n -pentanol >  i -pentanol >  i -butanol >  s -butanol >  n -butanol >  n -propanol >  i -propanol > ethanol. In easter solvents, the solubility of PP ranking as: ethyl formate > amyl acetate > butyl acetate > propyl acetate > ethyl acetate > isopropyl acetate. For ketone solvent, the solubility order is: cyclohexanone > 2-butanone > methyl isobutyl ketone. In other solvents, the solubility order is: THF > toluene > 1, 4‑dioxane > DMF. The maximum solubility of PP is 0.1922 mol·mol −1 (toluene, 353.15 K), and the minimum solubility is 0.0003788 mol·mol −1 (ethanol, 318.15 K). Four thermodynamic models, i.e., the modified Apelblat model, the Yaws model, the NRTL model and the Wilson model were selected to correlate the solubility data in this paper. NRTL model fits best among all the models with RAD no larger 4.84 × 10 −2 ( n -propanol) and RMSD value less than 12.55 × 10 −4 (1, 4-dioxane). Furthermore, dissolution thermodynamic properties of PP were evaluated based on the Wilson model. The dissolution process of PP is demonstrated to be spontaneous in the chosen organic solvents.